Influence of supplemental irrigation on annual ryegrass in southern Portugal - Lourenço, Maria Ermelinda V.L. (2006)
The objective of this research was to evaluate the effect of supplemental irrigation on increasing and stabilizing yield and quality of forage produced by annual ryegrass in Southern Portugal. The following four irrigation treatments were tested: rainfed (control), and irrigation up to 25%, 50% and 100% of soil water holding capacity. The results showed that irrigation doubled the number of harvests, four instead of two with the rainfed treatment, and also double the yields of dry matter, crude protein and dry matter digestibility which shows the importance of supplemental irrigation in stabilizing forage availability along the year, even at the lowest level of irrigation used. The differences between the control and the irrigation treatments were more noticeable with respect to crude protein yield.